Adhesive Capsulitis in Eight Dogs: Diagnosis and Management - Carr, Brittany J.; Canapp, Sherman O.; Canapp, Debra A.; Gamble, Lauri-Jo; Dycus, David L. (Frontiers in Veterinary Science, 2016)
ABSTRACT: Objective: To describe clinical and diagnostic findings as well as management of adhesive capsulitis in dogs. Background: Adhesive capsulitis, also known as frozen shoulder, is a syndrome defined by loss of range of motion of the shoulder and may be the end-stage manifestation of several primary conditions. Evidentiary Value: This is a case report series of eight dogs with chronic forelimb lameness diagnosed with adhesive capsulitis. Methods: Medical records (June 1, 2010 to September 1, 2015) including, physical examination findings, radiographic findings, magnetic resonance imaging findings, arthroscopy findings, and treatment plans were reviewed. Results: All dogs presented with a chronic, grade III-VI/VI forelimb lameness. On orthopedic examination all dogs had moderate to significant discomfort on shoulder extension and flexion and severe restriction of range of motion. Six of the eight dogs had evidence of bone remodeling and sclerosis in the affected shoulder on radiographs. Six of had an initial diagnostic ultrasound performed, which revealed evidence of fibrous scar tissue. Five dogs had magnetic resonance imaging performed that revealed moderate shoulder effusion and enhancement of the synovial lining of the shoulder. Arthroscopy was performed in five of the eight patients. Three were noted to have significant contracture, adhesions and fibrous scar tissue of the joint capsule. Severe inflammation was noted throughout the synovium of two patients. All eight patients tried conservative management consisting of oral medications and rehabilitation therapy. Five of the eight patients received extracorporeal shockwave therapy. Three patients received regenerative medicine treatment in the affected supraspinatus and shoulder. Regardless of the treatment elected, none of the dogs were reported to have significant improvement. Conclusion: Adhesive capsulitis is an uncommon cause of chronic forelimb lameness. Further investigation is needed to describe the etiology and pathogenesis of adhesive capsulitis in dogs to evaluate the effectiveness of both non-surgical and surgical treatment modalities, establish treatment protocols, and evaluate short- and long-term clinical outcome of patients. Application: Adhesive capsulitis should be considered in patients with chronic forelimb lameness and moderate to significant discomfort and restriction on shoulder range of motion.